Structure of Heteropentameric GABAA Receptors and Receptor-Anchoring Properties of Gephyrin - Kasaragod, Vikram Babu; Schindelin, Hermann (Frontiers in Molecular Neuroscience, 2019)
Gamma-aminobutyric acid type A receptors (GABA(A)Rs) mediate the majority of fast synaptic inhibition in the central nervous system (CNS). GABAARs belong to the Cys-loop superfamily of pentameric ligand-gated ion channels (pLGIC) and are assembled from 19 different subunits. As dysfunctional GABAergic neurotransmission manifests itself in neurodevelopmental disorders including epilepsy and anxiety, GABAARs are key drug targets. The majority of synaptic GABA(A)Rs are anchored at the inhibitory postsynaptic membrane by the principal scaffolding protein gephyrin, which acts as the central organizer in maintaining the architecture of the inhibitory postsynaptic density (iPSD). This interaction is mediated by the long intracellular loop located in between transmembrane helices 3 and 4 (M3-M4 loop) of the receptors and the universal receptor-binding pocket residing in the C-terminal domain of gephyrin. In 2014, the crystal structure of the beta3-homopentameric GABA(A)R provided crucial information regarding the architecture of the receptor; however, a clear understanding of the structure and assembly of heteropentameric receptors, as well as the mechanism of action of these receptors, remained enigmatic. This review will highlight recent advances in understanding the structure of heteropentameric synaptic GABA(A)Rs and how these structures have provided fundamental insights into the assembly of these multi-subunit receptors as well as their modulation by diverse ligands including the physiological agonist GABA. We will further discuss the role of gephyrin in anchoring of synaptic GABAARs and also glycine receptors, thus maintaining the architecture of the iPSD. Finally, we will also summarize how anti-malarial artemisinin drugs modulate gephyrin-specific inhibitory neurotransmission.